Distributed strain measurements in a CFA pile using high spatial resolution fibre optic sensors. (1st April 2018) - Bersan, Silvia; Bergamo, Otello; Palmieri, Luca; Schenato, Luca; Simonini, Paolo
Highlights: Strain measurements with 10 mm spatial resolution were performed along a pile. High spatial resolution enabled identifying local variations of pile axial stiffness. Identification of local effects led to sound analysis of strain data. Load-transfer curves were derived combining 1-d FEM and least square optimization. Abstract: Static load tests on fully instrumented piles are a useful tool for optimizing the design of pile foundations. By measuring the change in strain along a test pile it is possible to estimate pile-soil interface properties and infer site-specific and technology-specific load-transfer curves to be adopted for design. This paper presents strain measurements obtained from a distributed sensor installed in a continuous flight auger (CFA) pile undergoing a static load test. Distributed sensing was performed using optical frequency domain reflectometry (OFDR), which provided a spatial resolution of 10 mm. The high spatial resolution allowed to highlight local defects, as those produced by undesired variations in the pile cross-section area that can lead to erroneous data analysis if not fully understood. The paper also presents an approach for the derivation of load-transfer curves from continuous strain data.